Valorization of carbon dioxide (CO2) to enhance production of biomass, biofuels, and biorenewables (B3) in Chlorella saccharophila UTEX247: a circular bioeconomy perspective. (1st October 2021) - Kareya, Mukul Suresh; Mariam, Iqra; Rajacharya, Girish Halemirle; Nesamma, Asha Arumugam; Jutur, Pannaga Pavan
Abstract: Carbon dioxide supplementation regulates the metabolism of photosynthetic organisms, initiating CO2 fixation through the central carbon metabolism and partitioning the carbon in various metabolic processes. It is important to understand the molecular mechanisms of carbon fixation and partitioning to control and regulate biomass and lipid production. In this context, we investigated the metabolic and physiological responses of a freshwater microalga, Chlorella saccharophila, supplemented with very low CO2 (VLC) (300 ppm or 0.03%) and high CO2 (HC) (30 000 ppm, or 3% v/v), for its potential as a biorefinery strain. Our results demonstrate that growth with HC was enhanced 1.4‐fold in comparison with VLC. We speculate that growth with VLC was supported by the central electron flow. Similar changes were observed in various biochemical constituents, i.e., lipids, proteins and carbohydrates. It was also observed that the total pigment productivity was 1.8‐fold higher with HC supplementation than in cultures supplemented with VLC, further indicating enhanced growth in HC. Applying qualitative metabolomics, we identified nearly 23 essential metabolites. There was an accumulation of sugars and antioxidants such as trehalose and α‐tocopherol in VLC as compared to HC. In conclusion, our objective is to understand HC supplementation in C. saccharophila UTEX247 and to provide valuable insights leading to enhanced biomass for the production of biofuels and high‐value biorenewables (B 3 ) in the context of a circular bioeconomy by the valorization of carbon dioxide (CO2 ). © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd